2017
DOI: 10.1177/0148607117711387
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the Provision and Assessment of Nutrition Support Therapy in the Pediatric Critically Ill Patient: Society of Critical Care Medicine and American Society for Parenteral and Enteral Nutrition

Abstract: This document represents the first collaboration between 2 organizations-the American Society for Parenteral and Enteral Nutrition and the Society of Critical Care Medicine-to describe best practices in nutrition therapy in critically ill children. The target of these guidelines is intended to be the pediatric critically ill patient (>1 month and <18 years) expected to require a length of stay >2-3 days in a PICU admitting medical, surgical, and cardiac patients. In total, 2032 citations were scanned for relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
515
1
52

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 354 publications
(615 citation statements)
references
References 106 publications
7
515
1
52
Order By: Relevance
“…We did not formally appraise the quality of these papers, as our aim was to describe the definition and use of the term feeding intolerance. A further 32 papers were review or discussion papers [n = 6] [2, 6,13,18,46,47], surveys [n = 5] [16,40,41,43,44], research papers which support this review but are not included in papers which defined feeding intolerance [n = 19] [3, 8, 11, 12, 14, 15, 17, 24, 25, 27, 30-32, 36, 38, 39, 42, 49], and guidelines [n = 2] [4,26] where feeding intolerance was mentioned or discussed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not formally appraise the quality of these papers, as our aim was to describe the definition and use of the term feeding intolerance. A further 32 papers were review or discussion papers [n = 6] [2, 6,13,18,46,47], surveys [n = 5] [16,40,41,43,44], research papers which support this review but are not included in papers which defined feeding intolerance [n = 19] [3, 8, 11, 12, 14, 15, 17, 24, 25, 27, 30-32, 36, 38, 39, 42, 49], and guidelines [n = 2] [4,26] where feeding intolerance was mentioned or discussed.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, a more relaxed definition of feeding intolerance could also potentially lead to unsafe feeding practices. The latest ASPEN guidance [26] acknowledges feeding intolerance as a common barrier and only suggests the use of protocols that guide the detection and management of EN intolerance should be used; however, no guidance on how best to do this is made. The ESPGHAN nutrition committee 2010 position statement on practical approach of enteral nutrition in children (outside the PICU) highlighted diarrhea, nausea, vomiting, and regurgitations or aspirations as the major signs of enteral nutrition complications in children [4].…”
mentioning
confidence: 99%
“…This work showed that the expenditure of energy by organisms can be measured directly by direct calorimeters or estimated by measuring oxygen consumption (O 2 ): indirect calorimetry (4) (Figure 1). Indirect calorimetry is now considered the reference standard for measurement of energy expenditure in critically ill children (5). It is particularly recommended in children with nutritional deficits or derangements due to underlying disorders like cancers or acute diseases like sepsis or multiple trauma that are associated with large inaccuracies in estimation of energy needs, and those who fail attempts at liberation from mechanical ventilation (58).…”
Section: Introductionmentioning
confidence: 99%
“…All critically ill patients are susceptible to under and over nutrition, hence measurement of energy expenditure and the titration of intake based on the results is recommended (5). However, indirect calorimetry has suffered from limited spread that could be related to the high monetary cost to purchase and maintain the equipment, and the time cost to perform the measurement (58).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation